Pengaruh Penggunaan Media Edukasi Kesehatan Tentang Anemia: Literature Review - Ajeng Ayu Mahira; Friska Realita (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Background: Anaemia is a common health problem in adolescent girls that can affect concentration, growth and overall health. Digital media-based health education is a potential strategy to increase awareness and knowledge about anaemia. Objectives: This article aims to analyse the effectiveness of various digital educational media in improving adolescent girls' understanding of anaemia prevention. Methods: This review is based on a review of five studies with quasi-experimental approaches and randomised clinical trials that measured changes in knowledge, attitudes, and biological indicators of anaemia before and after educational interventions. Results: Education using TikTok media increased the mean score from 21.55 to 24.85 (p=0.000), while infographics increased from 18.90 to 25.50 (p=0.000). Podcasts increased knowledge scores from 76.94±12.49 to 88.71±12.51 (p=0.000) and attitudes (p=0.036). Digital games significantly increased Hb (p<0.001), but did not affect serum iron (p=0.35). Educational leaflet increased the good knowledge category from 0% to 83.33% (p=0.02), and HBM-based animated video increased the score from 94 to 102 (p=0.000). Conclusion: Interactive digital media was effective in improving adolescents' knowledge about anaemia compared to traditional media.